Major differences in organization and availability of health care and medicines for HIV/TB coinfected patients across Europe. Issue 9 (11th May 2015) - Mansfeld, M; Skrahina, A; Shepherd, L; Schultze, A; Panteleev, AM; Miller, RF; Miro, JM; Zeltina, I; Tetradov, S; Furrer, H; Kirk, O; Grzeszczuk, A; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to investigate the organization and delivery of HIV and tuberculosis (TB) health care and to analyse potential differences between treatment centres in Eastern (EE) and Western Europe (WE). Methods Thirty‐eight European HIV and TB treatment centres participating in the TB:HIV study within EuroCoord completed a survey on health care management for coinfected patients in 2013 (EE: 17 respondents; WE:21; 76% of all TB:HIV centres). Descriptive statistics were obtained for regional comparisons. The reported data on health care strategies were compared with actual clinical practice at patient level via data derived from the TB:HIV study. Results Respondent centres in EE comprised: Belarus (n = 3), Estonia (1), Georgia (1), Latvia (1), Lithuania (1), Poland (4), Romania (1), the Russian Federation (4) and Ukraine (1); those in WE comprised: Belgium (1), Denmark (1), France (1), Italy (7), Spain (2), Switzerland (1) and UK (8). Compared with WE, treatment of HIV and TB in EE are less often located at the same site (47% in EE versus 100% in WE; P < 0.001) and less often provided by the same doctors (41% versus 90%, respectively; P = 0.002), whereas regular screening of HIV‐infected patients for TB (80% versus 40%, respectively; P = 0.037) and directly observed treatment (88% versus 20%, respectively; P < 0.001) were more common in EE. The reported availability of rifabutin and second‐ and third‐line anti‐TB drugs was lower, and opioid substitution therapy (OST) was available at fewer centres in EE compared with WE (53% versus 100%, respectively; P < 0.001). Conclusions Major differences exist between EE and WE in relation to the organization and delivery of health care for HIV/TB‐coinfected patients and the availability of anti‐TB drugs and OST. Significant discrepancies between reported and actual clinical practices were found in EE.